PENGAKUAN PENDAPATAN DAN BEBAN SERTA PENGARUHNYA TERHADAP KEWAJARAN PENYAJIAN LAPORAN KEUANGAN PT. MITRA ANDALAN SATKOMINDO - Rini Meilinda; Budi Tri Rahardjo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
This research was conducted at PT Mitra Andalan Satkomindo which has applied the cash basis method in recognition of income and costs that are not in accordance with Financial Accounting Standards. There is a discrepancy in the presentation of financial statements because the company only presents the income statement. Then there is also a discrepancy in the treatment of recognition of income and expenses between Financial Accounting Standards. The results showed that in terms of recognition of income and costs using the accrual basis method. Recording of revenue and expense recognition based on cash basis is not in accordance with the Financial Accounting Standards because income and expenses are not recognized in the period that should be reported.